Human rights violation and political persecution in Bangladesh: the current scenery - Jalil, Md Abdul; Rahman, Muhammad Khalilur (Canadian Center of Science and Education, 2011)
Bangladesh emerged as an independent country in the South Asia in 1971 after being separated from Pakistan. In 1971 it was a very poor country. The general people had a hope and dream that the political parties will develop the country and will eradicate poverty gradually, will provide jobs to the 50% unemployed people, will educate the 60% illiterate people; but their holy hope and dream have not been fulfilled due to frequent hostile political culture, beating, killing among the political party members, no patriotism among the political leaders, massive corruption, unnecessary frequent strike, unnecessary opposition to the government policy etc. This paper has narrated the past and current social and political situation in Bangladesh briefly with the help of data collected from newspapers and statements given by intellectuals and political leaders. Descriptive and analytical research methodology has been applied in this paper to narrate the situation.